Molecular and in vitro characterization of field isolates of bovine herpesvirus-1. (2012)
Bovine Herpesvirus-1 (BoHV-1) is distributed worldwide and is a major pathogen in cattle, being the causal agent of a variety of clinical syndromes. The aim of this study was to isolate and to characterize (molecular and biological characterization) BoHV-1 from 29 immunosuppressed animals. It was possible to obtain 18 isolates, each from a different animal, such as from the respiratory and reproductive tracts. In some cases the cytopathic effect was visible 12 hours post-inoculation, and became characteristic after 36-48 hours. Biological characteristics were evaluated and compared with Iowa and Colorado-1 reference strains, and differences were found in plaque size, virus titer measured by TCID50 and PFU/mL, and one step virus curves. These results showed that some isolates had a highly virulent-like behavior in vitro, compared to the reference strains, with shorter eclipse periods, faster release of virus into the supernatants, and higher burst size and viral titer. There were no differences in glycoprotein expression of BoHV-1 isolates, measured by Western blot on monolayers. Moreover, using restriction endonucleases analysis, most of the viruses were confirmed as BoHV-1.1 and just one of them was confirmed as BoHV-1.2a subtype. These findings suggest that some wild-type BoHV-1 isolates could be useful as seeds to develop new monovalent vaccines.